An investigation of the determinants of the spatial characteristics of figure placements - Edwards, David J A (Rhodes University, Faculty of Humanities, Department of Psychology, 1973)
The doll placement technique is a projective instrument which yields objective measures from which inferences may be drawn. Subjects place pairs of dolls to represent social encounters described to them by the experimenter. When the dolls have been placed, the distance between them and the angles at which they stand can serve as a source of information either about the personality of the placer or about the way in which he perceives the relationship between the interactors represented. Most experimental work employing figure placements has used flat felt figures which subjects have mounted on a flannel graph. This method limits an investigator to one dependent variable, the inter-figure distance. However if three dimensional dolls are placed three dependent measures can be derived from a placement, one of distance and two of orientation. It has been demonstrated that a reliable correlation exists between the spatial relations between figures placed by a person and the spatial relationships between real interactors. The theoretical analysis of the determinants of interpersonal distance and orientation in social encounters which has been worked out by students of non-verbal behaviour is therefore able to serve as a basis for the interpretation of the spatial characteristics of doll placements. Previous work with the doll placement technique has concentrated on the distance between dolls. The present study explored the determinants of figure orientations. Firstly an analysis was made of the types of orientation pattern that can occur when two persons are involved in a social encounter. Secondly, an experiment was performed which was designed to explore whether asymmetry in an orientation pattern might act as a cue to determine how individual figures in a pair were perceived. Thirdly, two doll placement studies were performed which were designed to investigate the conditions giving rise to asymmetrical orientation patterns and the determinants of direct and indirect orientations. The confidence or anxiety attributed to an interactor represented by a figure proved to be a major determinant of its spatial position. The results of the study indicate that the use of the angle measures in the analysis of doll placements considerably enhances the value of the technique. It is argued that the doll placement method could be profitably employed both as a clinical instrument and as a research tool for cross-cultural psychology.
Keywords: Characters and characteristics; Psychology, Applied; Cross-cultural studies